Hiram Collins Haydn papers - Haydn, Hiram Collins, 1907-1973.; Haydn, Hiram Collins, 1907-1973.; Haydn, Hiram Collins, 1907-1973.; Haydn, Hiram Collins, 1907-1973.
Correspondence, memoranda, speeches, drafts and proofs of Haydn's published and unpublished works, articles, scripts, book reviews, financial and legal records, and other papers relating chiefly to his books and writings. Also includes material relating to his work as editor with Atheneum, Bobbs-Merrill Company, Crown Publishers, and Random House; and to his editing of two series, Makers of the American Tradition Series and Twentieth Century Library. Includes drafts of Haydn's books titled The Hands of Esau (1962), Report from the Red Windmill (1967), and Words & Faces (1974).
Author, editor, educator, and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Atheneum (New York, N.Y.); Bobbs-Merrill Company; Crown Publishers; Random House (Firm); American literature; Editing; Publishers and publishing -- United States; Authors; Editors; Educators; Publishers